Pengaruh Produk Skincare Berbahan Lidah Buaya Terhadap Kulit Berjerawat - Kamil, Laras Nurhidayati; Illahi, Elsa Rahmi (Jurnal Tata Rias, 2024)
Cosmetic products contain various ingredients that may potentially cause skin irritation, especially in individuals with sensitive or acne-prone skin. One of the natural ingredients commonly used is aloe vera, which is rich in components such as vitamin A and vitamin C. These vitamins provide benefits for maintaining moisture in dry skin, preventing premature aging, and supporting facial care for acne-prone skin. This research aims to review the effects of aloe vera on acne-prone skin and identify the active components found in aloe vera. The chosen method aims to gain a deep understanding of the issues, theories, and findings from previous studies. The process begins with identifying the problem and research objectives, which serve as the foundation for determining the main focus and sub-themes to be studied. Its anti-inflammatory properties are highly beneficial in reducing inflammation in the body, whether on the skin or internal tissues. This makes aloe vera effective for treating wounds, skin irritation, and inflammation caused by infections or allergies. Its ability to reduce inflammation also makes it a good option for addressing various skin issues, such as acne or dermatitis. Aloe vera aids in the regeneration of cells, accelerates skin healing, and maintains skin moisture. With all its benefits, aloe vera is a highly valuable raw material in both the medical and beauty fields. Findings indicate that aloe vera-based skincare products can be an effective and safe alternative for treating acne-prone skin, with active components supporting the reduction of inflammation and bacteria.